Challenges and recommendations for high quality research using electronic health records - K Honeyford; K Honeyford; P Expert; P Expert; E.E Mendelsohn; B Post; B Post; A.A Faisal; A.A Faisal; A.A Faisal; A.A Faisal; B Glampson; et al. (Frontiers Media S.A., 2022)
Harnessing Real World Data is vital to improve health care in the 21st Century. Data from Electronic Health Records (EHRs) are a rich source of patient centred data, including information on the patient's clinical condition, laboratory results, diagnoses and treatments. They thus reflect the true state of health systems. However, access and utilisation of EHR data for research presents specific challenges. We assert that using data from EHRs effectively is dependent on synergy between researchers, clinicians and health informaticians, and only this will allow state of the art methods to be used to answer urgent and vital questions for patient care. We propose that there needs to be a paradigm shift in the way this research is conducted - appreciating that the research process is iterative rather than linear. We also make specific recommendations for organisations, based on our experience of developing and using EHR data in trusted research environments.